Farmer Census Survey in north west region (Rajshahi and Rangpur) of Bangladesh - Khondker, Murshed-E-Jahan; Asgar Alam, Md. Abu Jafar; Biswas, Ashutosh; Ara, Ismat; Tabassum, Sumaya (2023)
This census survey of fish farmers provides an overview of the basic demographics of smallholder fish farmers of Rajshahi and Rangpur division who are directly associated with the IDEA project. In total, 43,173 smallholder farmers participated in the census and the data generates information about general characteristics of fish farmers encompassing few crucial attributes such as productivity, land size and fish consumption from own production.